Pengembangan Multimedia Pembelajaran Interaktif Berbasis Video Terhadap Materi Sejarah Kebudayaan Islam Abu Bakar As-Shiddiq Sang Pembenar Kelas V MI/SD - Dina Safira; Hamdan Husein Batubara (Jurnal IAI Bunga Bangsa Cirebon, 2021)
This study aims to determine the development of video-based interactive learning multimedia on the material of SKI Abu Bakar As-Shiddiq, the corrector of class V MI / SD. Learning media as a part of the learning system must be in accordance with the learning components. The goal is to be optimal in facilitating learning activities. This article aims to explain video-based interactive learning on the SKI material of Abu Bakar As-Shiddiq, the class V MI / SD correct. This study uses the ADDIE model. ADDIE is an overview Analyze, Design, Develop, Implement, and Evaluate the process applied to instructional design in order to generate learning. The steps in the research and development design (Research and Development) are described in accordance with the development procedure in designing a learning system. The source of the data needed is primary data by distributing questionnaires. Parties related to the research being carried out, namely the material experts, media experts, and the students concerned. The subjects of this study were students of PGMI 6C UIN Walisongo Semarang. The results of the validation of categorical good learning and interactive videos are suitable for learning. Abstrak Penelitian ini bertujuan untuk mengetahui pengembangan multimedia pembelajaran interaktif berbasis video terhadap materi SKI Abu Bakar As-Shiddiq sang pembenar kelas V MI/SD. Media pembelajaran sebagai salah satu bagian sistem pembelajaran harus sesuai dengan komponen pembelajaran. Tujuannya agar optimal dalam memfasilitasi kegiatan pembelajaran. Artikel ini bertujuan untuk menjelaskan pembelajaran interaktif berbasis video terhadap materi SKI Abu Bakar As-Shiddiq sang pembenar kelas V MI/SD. Penelitian ini menggunakan model ADDIE. ADDIE adalah an overview Analyze, Design, Develop, Implement, and Evaluate process applied to instructional design in order to generate of learning. Langkah-langkahnya desain penelitian dan pengembangan (Research and Development) yang dijabarkan sesuai dengan prosedur pengembangan dalam merancang sistem pembelajaran. Sumber data yang diperlukan adalah data primer dengan cara menyebarkan angket. Pihak yang berhubungan dengan penelitian yang dilakukan, yaitu dengan ahli materi, ahli media, dan mahasiswa yang bersangkutan. Subjek penelitian ini adalah mahasiswa PGMI 6C UIN Walisongo Semarang. Hasil validasi terhadap pembelajaran berkatagori baik dan video interaktif layak digunakan untuk pembelajaran.